Effects of vitamin E supplementation on exercise-induced oxidative stress: a meta-analysis - Stepanyan, V.; Crowe, M.; Haleagrahara, N.; Bowden, B. (Applied Physiology, Nutrition, and Metabolism, 2014)
Tocopherols (commonly referred to as "vitamin E") are frequently studied antioxidants in exercise research. However, the studies are highly heterogeneous, which has resulted in contradicting opinions. The aim of this review is to identify similar studies investigating the effects of tocopherol supplementation on exercise performance and oxidative stress and to perform minimally biased qualitative comparisons and meta-analysis. The literature search and study selection were performed according to Cochrane guidelines. A 2-dimensional study execution process was developed to enable selection of similar and comparable studies. Twenty relevant studies were identified. The high variability of study designs resulted in final selection of 6 maximally relevant studies. Markers of lipid peroxidation (malondialdehyde) and muscle damage (creatine kinase) were the 2 most frequently and similarly measured variables. Meta comparison showed that tocopherol supplementation did not result in significant protection against either exercise-induced lipid peroxidation or muscle damage. The complex antioxidant nature of tocopherols and low accumulation rates in muscle tissues could underlie an absence of protective effects.